WWOX, A NEW POTENTIAL TUMOR SUPPRESSOR GENE - Hezova, Renata; Ehrmann, Jiri; Kolar, Zdenek (Biomedical papers, 2007)
Background: WWOX (WW domain-containing oxidoreductase) gene, located on chromosome 16q 23.3-24.1 in the region recognized as the common fragile site FRA16D is considered to be a tumor suppressor gene involved in various cancers: breast, ovarian, prostate, esophageal, lung, pancreatic, gastric and hepatic. The aim of this study was to describe (i) putative protein interactions of WWOX (ii) the molecular mechanisms of tumor suppressor activity (iii) present an overview of WWOX in relation to nervous system and breast, prostate and ovarian cancers.Methods and Results: WWOX expression is up-regulated in endocrine organs indicating its importance in these tissues. In many cancers WWOX expression is down-regulated and low WWOX expression is related to poor prognosis.Conclusion: All the evidence suggest that WWOX can be considered as a new tumor suppressor gene and target for gene therapy due to the association of high WWOX expression with improved disease free survival.
Keywords: WWOX/Tumor suppressor/Steroid dependent cancers/Nervous system